Right-sided diaphragmatic hernia with hepatic herniation after blunt trauma: Report of two cases of early diagnosis and treatment - Isabella Martelli Rocca; Luiz Scaglione; Bianca Argentino; Vinicius Teixeira; José Mauro Silva Rodrigues; Marcelo A.F. Ribeiro, Jr. (Trauma Case Reports)
Traumatic diaphragmatic hernia (TDH) is an uncommon condition resulting from high-energy blunt trauma or penetrating injuries. Right-sided TDH accounts for a small proportion of diaphragmatic ruptures. Early diagnosis remains a major challenge, with a significant number of cases diagnosed late, which increases morbidity and mortality by a substantial increase. Computed tomography (CT), particularly for right-sided TDH, is a diagnostic modality with high sensitivity and specificity. We report two cases of right-sided TDH with hepatic herniation following blunt trauma. The first case involved a 30-year-old male who sustained high-energy trauma in a motor vehicle collision. Hemodynamically stable, he underwent CT imaging that confirmed the diagnosis. He was treated via laparotomy with surgical repair and had a prolonged ICU stay due to rhabdomyolysis and pneumonia, ultimately discharged in good condition. The second case involved a 72-year-old female pedestrian struck by a bus. She also presented hemodynamically stable, underwent CT, and received early surgical repair via laparotomy. She was discharged on postoperative day three with favorable recovery. These cases highlight the importance of high clinical suspicion based on trauma mechanism, the role of CT in stable patients, and the value of early diagnosis and surgical management in achieving favorable outcomes. At one-year follow-up, the patient remained asymptomatic, with no recurrence or functional respiratory limitations on clinical examination.